PENGARUH GAYA KEPEMIMPINAN DAN KOMUNIKASI PIMPINAN TERHADAP KINERJA PEGAWAI MELALUI MOTIVASI KERJA PADA DINAS KOPERASI DAN UMKM KABUPATEN JEMBER - Pradana, Lufi Rizki; Setyanti, Sri Wahyu Lelly Hana; Endhiarto, Tatok (BISMA: Jurnal Bisnis dan Manajemen, 2016)
Abstract: This study aims to examine the impact of communication led to employee performance through motivation to work in the Department of Cooperatives and UMKM JemberDistrict. The research approach used in this study are quantitatively using explanatory research. This study population all civil servants Department of Cooperatives and UMKM Jember District with sampling technique using saturation sampling (census) with 38 respondents. Data analysis method used is the analysis of the path (Path Analysis). The test results and data analysis were performed with SPSS show that (1) leadership style influence directly and significantly on work motivation of employees, (2) communication leadership influence directly and significantly on work motivation of employees, (3) leadership style has no effect directly and significantly to the performance of employees, (4) communication led direct and significant impact on the performance of employees, (5) work motivation direct and significant impact on the performance of employees, (6) leadership style on employee performance positive and significant impact through work motivation employees, (7) communication led to employee performance through a positive and significant impact employee motivation at the Department of Cooperatives and UMKM Jember District. Keywords: Leadership Style, Communications Leader, Work Motivation, Performance